2015
DOI: 10.1089/jir.2014.0184
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Beta, a Decisive Factor in Angiogenesis and Arteriogenesis

Abstract: In this review we discuss the current literature on the effects of type I interferons (IFN) and their downstream effectors on vascular growth in experimental models in vitro and in vivo. In addition to its well-documented role in angiogenesis, that is, the growth of new capillaries from existing vessels, we will also describe emerging evidence and mechanisms by which type I IFN may inhibit arteriogenesis, that is, the expansive remodeling of existing collateral arteries. Crucial in both processes is the common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…Alternatively, the presence of physiologic blood flow may have significant crosstalk with antibody engagement of PECAM-1, which is itself a component of the endothelial mechanosensory complex 39 , and could negate some of the effects seen in other experimental settings. Of note, CEPAL antibodies did result in significant elevations of two pro-inflammatory cytokines, GM-CSF and IFN-β, both of which play significant roles in angiogenesis 40 , 41 . While of unclear significance, these cytokines and pro-angiogenic pathways will require close examination in future translational studies involving CEPAL-based therapies.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, the presence of physiologic blood flow may have significant crosstalk with antibody engagement of PECAM-1, which is itself a component of the endothelial mechanosensory complex 39 , and could negate some of the effects seen in other experimental settings. Of note, CEPAL antibodies did result in significant elevations of two pro-inflammatory cytokines, GM-CSF and IFN-β, both of which play significant roles in angiogenesis 40 , 41 . While of unclear significance, these cytokines and pro-angiogenic pathways will require close examination in future translational studies involving CEPAL-based therapies.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study has also shown that Fli1 and its close homolog Erg1, transcriptionally control IFN-β gene in pulmonary ECs; thus, endothelial Fli1 and Erg1 deficiency leads to activation of IFN-β and its target genes in ECs (58). IFN-β is known to have potent anti-angiogenic effects (59).…”
Section: Microvasculopathymentioning
confidence: 99%
“…165 In addition, treatment of endothelial cells with IFN-γ can selectively augment the migration of Th1 cells, the subtype of T cells that promotes cellular immunity. 166 Apart from endothelial cells, tumor vasculature also plays a crucial role in the process of trafficking and infiltration of T cells. However, IFNs, as anti-angiogenic cytokines, 167 may restrict the construction of vessels in the TME and thus make it difficult for T cell trafficking.…”
Section: Ifns Promote Trafficking and Infiltration Of T Cellsmentioning
confidence: 99%
“…165 In addition, treatment of endothelial cells with IFN-γ can selectively augment the migration of Th1 cells, the subtype of T cells that promotes cellular immunity. 166 …”
Section: Ifns Regulate the Cancer-immunity Cyclementioning
confidence: 99%